The incremental validity of a Situational Judgement Test (SJT) relative to personality and cognitive ability to predict managerial performance - Fertig, Siglind (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2009.